The Influence of Food-Based Contextual Experiments on Students’ Understanding of Chemical Reaction Concepts - Kamaliana, Yola; Ahmadi, Ahmadi (Multi Discere Journal, 2023)
This study investigates the influence of food-based contextual experiments on students’ understanding of chemical reaction concepts. Chemical reactions are fundamental topics in chemistry; however, students often experience difficulties in understanding reaction processes because they involve macroscopic observations, symbolic equations, and submicroscopic particle interactions. Food-based contextual experiments were used as an instructional strategy to connect abstract chemical reaction concepts with familiar materials found in students’ daily lives, such as vinegar, baking soda, milk, salt, sugar, and fermented food products. This study employed a pre-experimental design using a one-group pretest–posttest format. The participants consisted of 31 Grade X students at Pondok Pesantren Nurul Hakim Kediri. Data were collected through a conceptual understanding test consisting of five items related to indicators of chemical reaction concepts, including evidence of chemical reactions, reactants and products, conservation of mass, reaction types, and factors affecting reactions. The data were analyzed using descriptive statistics and a paired-sample t-test. The findings showed that students’ conceptual understanding significantly improved after learning through food-based contextual experiments compared with their initial understanding. The learning activities enabled students to observe real chemical phenomena, discuss reaction evidence, and relate experimental results to chemical equations. These findings suggest that food-based contextual experiments can serve as an effective contextual learning approach to improve students’ understanding of chemical reaction concepts.